Novel preclinical and radiopharmaceutical aspects of (68Ga)Ga-PSMA-HBED-CC: a new PET tracer for imaging of prostate cancer - Eder, Matthias; Kiß, Oliver; Müller, Miriam; Bauder-Wüst, Ulrike; Remde, Yvonne; Schäfer, Martin; Hennrich, Ute; Eisenhut, Michael; Afshar-Oromieh, Ali; Haberkorn, Uwe; Kopka, Klaus (Pharmaceuticals, 2014)
The detection of prostate cancer lesions by PET imaging of the prostate-specific membrane antigen (PSMA) has gained highest clinical impact during the last years. 68Ga-labelled Glu-urea-Lys(Ahx)-HBED-CC ([68Ga]Ga-PSMA-HBED-CC) represents a successful novel PSMA inhibitor radiotracer which has recently demonstrated its suitability in individual first-in-man studies. The radiometal chelator HBED-CC used in this molecule represents a rather rarely used acyclic complexing agent with chemical characteristics favourably influencing the biological functionality of the PSMA inhibitor. The simple replacement of HBED-CC by the prominent radiometal chelator DOTA was shown to dramatically reduce the in vivo imaging quality of the respective 68Ga-labelled PSMA-targeted tracer proving that HBED-CC contributes intrinsically to the PSMA binding of the Glu-urea-Lys(Ahx) pharmacophore. Owing to the obvious growing clinical impact, this work aims to reflect the properties of HBED-CC as acyclic radiometal chelator and presents novel preclinical data and relevant aspects of the radiopharmaceutical production process of [68Ga]Ga-PSMA-HBED-CC.
Im Titel steht der Ausdruck (68Ga) in eckiger Klammer, die Zahl 68 ist dabei hochgestellt
Gesehen am 17.02.2021